2023
DOI: 10.3389/fimmu.2022.1029092
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between cuproptosis and ferroptosis regulators defines the tumor microenvironment for the prediction of prognosis and therapies in lung adenocarcinoma

Abstract: Cuproptosis, a newly identified form of programmed cell death, plays vital roles in tumorigenesis. However, the interconnectivity of cuproptosis and ferroptosis is poorly understood. In our study, we explored genomic alterations in 1162 lung adenocarcinoma (LUAD) samples from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) cohort to comprehensively evaluate the cuproptosis regulators. We systematically performed a pancancer genomic analysis by depicting the molecular correlations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In fact, a novel form of copper-dependent cell death that is triggered by copper ionophores, called cuproptosis, is accompanied by the accumulation of ROS and mitochondrial metabolism ( 13 , 14 ). Previous studies have identified several genes and lncRNAs related to cuproptosis in LUAD ( 20 , 21 , 45 47 ), and developed a cuproptosis signature that correlates with the prognosis and tumor microenvironment of LUAD patients ( 16 , 19 , 48 ). Therefore, cuproptosis may play an important role in LUAD and provide new insights into the treatment of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a novel form of copper-dependent cell death that is triggered by copper ionophores, called cuproptosis, is accompanied by the accumulation of ROS and mitochondrial metabolism ( 13 , 14 ). Previous studies have identified several genes and lncRNAs related to cuproptosis in LUAD ( 20 , 21 , 45 47 ), and developed a cuproptosis signature that correlates with the prognosis and tumor microenvironment of LUAD patients ( 16 , 19 , 48 ). Therefore, cuproptosis may play an important role in LUAD and provide new insights into the treatment of CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the occurrence of ferroptosis is due to the production of ROS by excessive free Fe 2+ under the action of Fenton reaction, which produce lipid peroxidation caused by oxidized lipids. Cuproptosis is a newly discovered programmed cell death caused by Cu 2+ as well ( Shen et al, 2023b ). Finally, accumulated research has found that some biological compounds have multiple effects in controlling malignant tumors, such as inducing autophagy to prevent apoptosis of malignant tumor cells.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…In addition, bioinformatics analyses have revealed a potential clinical connection between the FRGs and LUAD patients. A prognostic model integrating several FRGs was used to predict the prognosis, mutation burden, tumor microenvironment (TME) cell infiltration characteristics, immunotherapy effects, and chemotherapy sensitivities in patients with LUAD [32][33][34][35][36][37].…”
Section: Ferroptosis In Luad Progressionmentioning
confidence: 99%